2019
DOI: 10.1074/jbc.ra119.008310
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the amyloid precursor protein (APP) at Ser-675 promotes APP processing involving meprin β

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by abnormal deposition of β-amyloid (Aβ) peptides. Aβ is a cleavage product of the amyloid precursor protein (APP), and aberrant posttranslational modifications of APP can alter APP processing and increase Aβ generation. In the AD brain, seven different residues, including Ser-675 (APP695 numbering) in the APP cytoplasmic domain has been found to be phosphorylated. Here, we show that expression of a phosphomimetic variant of Ser-675 in APP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…AD has been extensively characterized by the gradual decline of neuronal health. Neurotoxins, TAU protein neurofibrillary tangles, amyloid-beta (Aβ) plaque accumulation in mature neuron phenotypes [1][2][3][4][5], mitochondria dysfunction (fusion-fission imbalance) [6,7], and neuroinflammation collectively involves in neurodegeneration in AD [8][9][10][11]. Mitochondrial dysfunction results in the accumulation of harmful reactive oxygen species (ROS), which subsequently trigger CNS apoptotic decline [7].…”
Section: Introductionmentioning
confidence: 99%
“…AD has been extensively characterized by the gradual decline of neuronal health. Neurotoxins, TAU protein neurofibrillary tangles, amyloid-beta (Aβ) plaque accumulation in mature neuron phenotypes [1][2][3][4][5], mitochondria dysfunction (fusion-fission imbalance) [6,7], and neuroinflammation collectively involves in neurodegeneration in AD [8][9][10][11]. Mitochondrial dysfunction results in the accumulation of harmful reactive oxygen species (ROS), which subsequently trigger CNS apoptotic decline [7].…”
Section: Introductionmentioning
confidence: 99%
“…We transiently transfected cells overexpressing APP695 with one of the following combinations of cDNA: (i) wt ADAM10 + EV; (ii) US-BS-TEVcs + TEV as negative control; (iii) BS-Cyt-TEVcs + EV; and (iv) BS-Cyt-TEVcs + TEV. The cell growth medium was analyzed to detect ADAM10-dependent release of soluble αAPP (sAPPα) fragment derived from α-secretase-mediated APP processing [ 45 , 46 ]. In Western blot analyses, we detected similar amounts of lysate loading control protein, allowing for a comparative analysis of its α-secretase activity on APP processing ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of APP at Tyr682 by Fyn tyrosine kinase promoted the APP translocated into acidic neuronal compartments where it is processed to generate Aβ (Iannuzzi et al, 2020). Phosphorylation of APP at Ser675 also altered the balance of APP-processing through increasing meprin β-mediated and decreasing α-secretase-mediated APP cleavage at the plasma membrane (Menon et al, 2019). Additionally, phosphorylation of APP at Thr668 promoted the APP transfer to the endosome where is cleaved by the BACE1 and subsequently promoted Aβ generation (Lee et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…When phosphorylation of APP at Thr668, the APP is a tendency to translocate to the endosomes where is an enrichment of BACE1, thus promoting the Aβ production; in contrast, mutation of APP at Thr668 or inhibition of p-APP(Thr668) expression decreased the Aβ production (Lee et al, 2003). Furthermore, a recent study also revealed that the phosphorylation of APP at Ser675 enhanced the Aβ production by promoting the meprin β-mediated APP-processing at the plasma membrane (Menon et al, 2019). These data suggest that inhibition of APP phosphorylation at specific sites is a promising strategy to repress Aβ production.…”
Section: Introductionmentioning
confidence: 99%